Prevention and Treatment of Cerebral Complications Associated with Thoracic Endovascular Aortic Repair - Miyamoto, Shinji (Japanese Journal of Vascular Surgery, 2022)
Brain complications after TEVAR are non-fatal but significantly reduce ADL and worsen long-term prognosis. Cerebral infarction due to porridge embolism is the main cause of them and it occurs several times more often than overt cerebral infarction. Diagnosis of the location of atheroma by preoperative CT and protective catheter and device manipulation considering it are important for prevention, but embolization cannot be completely prevented by those. Balloon occlusion or direct blockage of the cervical branch are effective as prophylaxis, and extracorporeal circulation can be used to completely separate the cerebral circulation from the systemic circulation. Treatment is different from normal cerebral infarction and thrombolysis or removal of emboli is not effective. Edaravone administration reduces the degree of brain damage and improves prognosis and should be used without hesitation immediately after onset.